2012
DOI: 10.1007/s11481-012-9400-1
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan Attenuated Inflammation and Combined Opioid Use in Humans Undergoing Methadone Maintenance Treatment

Abstract: Recent studies show that proinflammatory cytokines might be related to the development of opioid dependence (physiological, psychological, or both). In a double-blind, randomly stratified clinical trial investigating whether add-on dextromethorphan (60-120 mg/day) attenuated inflammation and the combined use of opioids in heroin-dependent patients undergoing methadone maintenance treatment, we evaluated whether inflammation is related to the progression of opioid dependence. All participants (107 heroin-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…The elevated systemic inflammation in IDUs that we observed is consistent with previous studies [ 16 , 17 , 87 89 ], and may contribute to co-morbidities within this population. Chronic inflammation is associated with cardiovascular disease, kidney disease, accelerated aging, and neurodegenerative diseases, all of which are increased among IDUs [ 4 , 74 79 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The elevated systemic inflammation in IDUs that we observed is consistent with previous studies [ 16 , 17 , 87 89 ], and may contribute to co-morbidities within this population. Chronic inflammation is associated with cardiovascular disease, kidney disease, accelerated aging, and neurodegenerative diseases, all of which are increased among IDUs [ 4 , 74 79 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have reported elevated inflammatory mediators associated with IDUs, including serum IL-1β, IL-6, and IL-8 in methadone-maintained IDUs [ 16 ] [ 17 ], and increased dendritic cell and natural killer cell activation in IDUs that is associated with needle sharing [ 18 ]. These findings suggest that multiple mediators may be contributing to altered immune homeostasis in IDUs.…”
Section: Introductionmentioning
confidence: 99%
“…inhibits inflammatory mediators, including cytokines (TNF-α, IL-1β and IL-6) and chemokines in sepsis mice model [ 53 ]. Furthermore, our recent clinical study showed that DM (60–120 mg/day, oral) attenuated plasma cytokine TNF-α, which has been increased in methadone-treated heroin addicts [ 54 ]. Our present study demonstrates that SNL induced high plasma levels of IL-6, IL-1β, and TNF-α, and chronic oxycodone (1 mg/kg, s.c.) suppressed all of them significantly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dextromethorphan antagonizes the spinal NMDA receptor system, and may manipulate opioid effects via this mechanism [186,187]. Several studies have shown mixed results with dextromethorphan as an adjuvant medication in treating opioid tolerance [188][189][190][191] and withdrawal symptoms [192][193][194][195][196][197]. Numerous studies have cited dextromethorphan's ability to reduce intra-and post-operative morphine consumption [198][199][200], while others have not replicated these findings [201,202].…”
Section: Dextromethorphanmentioning
confidence: 99%